1997
DOI: 10.1074/jbc.272.5.2744
|View full text |Cite
|
Sign up to set email alerts
|

Siroheme Biosynthesis in Higher Plants

Abstract: Siroheme, the prosthetic group for both nitrite and sulfite reductases, is a methylated, iron-containing modified tetrapyrrole. Here we report the first molecular characterization of the branch point enzyme in higher plants, which directs intermediates toward siroheme synthesis. A cDNA was cloned from Arabidopsis thaliana (UPM1) that functionally complements an Escherichia coli cysG mutant, a strain that is unable to catalyze the conversion of uroporphyrinogen III (Uro'gen-III) to siroheme. UPM1 is 1484 base p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…In Arabidopsis, this reaction is catalyzed by an SAM-dependent Urogen III methyltransferase encoded by UPM1 (At5g40850) (Leustek et al 1997). UPM1 encodes a 39.9-kDa protein containing two regions that are identical to consensus sequences found in bacterial Urogen III and precorrin methyltransferases encoded by SirA.…”
Section: Sam-dependent Urogen III Methyltransferasementioning
confidence: 99%
“…In Arabidopsis, this reaction is catalyzed by an SAM-dependent Urogen III methyltransferase encoded by UPM1 (At5g40850) (Leustek et al 1997). UPM1 encodes a 39.9-kDa protein containing two regions that are identical to consensus sequences found in bacterial Urogen III and precorrin methyltransferases encoded by SirA.…”
Section: Sam-dependent Urogen III Methyltransferasementioning
confidence: 99%
“…However, in other bacteria such as Bacillus megaterium, these activities are housed within three separate enzymes called SirA (uro'gen III methyltransferase), SirC (dihydrosirohydrochlorin dehydrogenase), and SirB (sirohydrochlorin ferrochelatase) (17). We had already shown that Arabidopsis contains a functional SirA orthologue UPM1 (14). Using the BLAST algorithm we were unable to identify orthologues in the Arabidopsis genome or in any plant EST data base of SirC.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme that catalyzes this reaction, uro'gen III methyltransferase (UPM1), requires S-adenosyl-L-methionine as a methyl donor and has been characterized from a wide variety of sources including eubacteria (10,11), Archaea (12), and higher plants (13,14). In Arabidopsis thaliana UPM1 has been localized to the chloroplast (14). To complete the synthesis of siroheme, dihydrosirohydrochlorin has to be oxidized to sirohydrochlorin and then chelated with ferrous iron.…”
mentioning
confidence: 99%
“…The results described here show that the biosynthesis of sirohaem can be accomplished with a two-enzyme system. Two-enzyme systems for sirohaem biosynthesis have been inferred from previous work on Bacillus megaterium [12] and in the higher plant Arabidopsis thaliana [35]. Recently sirohaem synthesis from uro'gen III in S. cere isiae has been shown to require two proteins, Met1 and Met8 [17], although the functions of the two proteins have not been accurately ascribed.…”
Section: B ) Seem To Operate Independentlymentioning
confidence: 99%
“…(a) Alignment of the predicted amino acid sequences of the uro'gen III transmethylase sequences (CysG A ) from Anacystis nidulans [42], Synechocystis sp. (accession number ss110378), Arabidopsis thaliana [35], Zea mays [43], Paracocccus denitrificans [44], Methanobacterium ivanovii [45], Methanococcus jannaschii [46], Bacillus subtilis [18], Bacillus megaterium [12], Bacillus stearothermophilus [47], Escherichia coli [13], Propioni freudenreichii [48] and Pseudomonas denitrificans [10]. The consensus sequence is shown and the mutated residues are marked by an asterisk.…”
Section: Enzyme Purificationmentioning
confidence: 99%